Expanding Citizen Science: Community Action Without Primary Data Collection. (20th March 2023) - Evans, Robert; Hacking, Nick; Lewis, Jamie
Environmental planning disputes often combine questions of regulation and legislation with distinctive, place-based epistemic issues that lend themselves to citizen science approaches. Whilst these citizen science activities often concern the enforcement of regulations, here we describe the attempts of a local community group to prevent the start-up of a new biomass incineration plant by showing that it fails to comply with the relevant regulations and/or that the associated legislation has not been applied correctly. Through documentary sources and in-depth interviews, we examine the ways in which the group's work has parallels with aspects of regulatory science. In describing this work, and thinking about how to categorise it, we argue that conceptions of citizen science need to be broadened to include a wider range of activities than the traditional focus on primary data collection.